Fatigue evaluation of rib-to-deck welded joint using averaged strain energy density method. (15th December 2018) - Luo, Pengjun; Zhang, Qinghua; Bao, Yi; Zhou, Aixin
Highlights: The SED method is used for fatigue evaluation of rib-to-deck welded joints. Fatigue test results are applied to validate the proposed SED method. Effect of weld geometrical variables on fatigue failure mode is evaluated. W-N curve is derived using the SED method to evaluate full-scale specimens. Abstract: This paper investigates the feasibility of an averaged strain energy density (SED) method for fatigue evaluation of rib-to-deck weld joint in orthotropic steel deck. The effect of weld geometry on fatigue resistance of rib-to-deck joint is evaluated. The analysis results of the presented average SED method are validated against fatigue testing data and compared with the results of the conventional hot-spot stress and effective notch stress methods. A W-N curve is derived using the averaged SED method and used for evaluating the fatigue strength of rib-to-deck welded joints. The averaged SED method is also used to investigate the effect of weld geometrical variables on the fatigue failure mode transition, and the fatigue strength of full-scale orthotropic steel deck specimens. The results indicate that the averaged SED method provides superior ability in evaluating fatigue resistance and failure mode of rib-to-deck welded joint.